Нефтегазовое дело. Книга для студентов: учебное пособие - Болсуновская Л. М. Людмила Михайловна; Абрамова Р. Н. Раиса Николаевна; Матвеенко И. А. Ирина Алексеевна; Терре Д. А. Дина Анатольевна; Долгая Т. Ф. Татьяна Федоровна; Бочарова Т. В. Татьяна Викторовна; Шендерова И. В. Инна Владимировна; Вершкова Е. М. Елена Михайловна; Малюкова Д. С. Дарья Сергеевна; Сухорукова Н. В. Надежда Витальевна (Томск, Изд-во ТПУ, 2015)
Заглавие с титульного экрана